2018
DOI: 10.3758/s13420-018-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Timmy’s in the well: Empathy and prosocial helping in dogs

Abstract: Dogs are thought to evaluate humans' emotional states, and attend more to crying people than to humming people. However, it is unclear whether dogs would go beyond focusing attention on humans in need by providing more substantive help to them. This study used a trapped-other paradigm, modified from use in research on rats, to study prosocial helping in dogs. A human trapped behind a door either cried or hummed, and the dog's behavioral and physiological responses (i.e., door opening and heart rate variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 49 publications
6
39
2
4
Order By: Relevance
“…These studies yielded limited evidence that opening the door constituted a prosocial behavior. Sanford et al [36] observed interesting trends in post-hoc comparisons but the primary findings of this study did not support the hypothesis that dogs prosocially rescued their owners. Considering only individuals that opened, dogs in the experimental condition opened faster.…”
Section: Introductioncontrasting
confidence: 88%
See 3 more Smart Citations
“…These studies yielded limited evidence that opening the door constituted a prosocial behavior. Sanford et al [36] observed interesting trends in post-hoc comparisons but the primary findings of this study did not support the hypothesis that dogs prosocially rescued their owners. Considering only individuals that opened, dogs in the experimental condition opened faster.…”
Section: Introductioncontrasting
confidence: 88%
“…To date, two studies have tested for prosocial rescue behavior in dogs. Sanford et al [36] used a modified version of the trapped-other paradigm to assess whether dogs would walk to their owner in an adjacent room, which required pushing through a small, windowed door. In the experimental condition, the owner pretended to cry and in the control condition, the owner hummed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Charles (2014) remarked that dogs can provide a sense of 'ontological security' that leads to a reciprocal feeling of kinship between canine and human that is rooted in 'connectedness and belonging' (p. 726). The personal cues that Diane showed and shared with Worry invited the unique traits of her dog-ness to attend to the very specific needs Diane sought: a non-judgmental and open friend to simply spend time with (Evans-Wilday et al, 2018;Sanford, Burt, & Meyers-Manor, 2018) And now that Diane is not a regular part of our lives any longer, I find myself even more in tune with this dog, something I never thought possible. We have always had wonderful chemistry-I love her like a kid-but now I look at her as the next aging friend I have to make sure has a rewarding last few years of life.…”
Section: Resultsmentioning
confidence: 99%